Smart Bag Carrier with Human Detection System - Shakib, Mohammad Lutfi; Mohamed Nasir, NoorHamizah (Evolution in Electrical and Electronic Engineering, 2021)
In recent years, robot technology has developed significantly. This project is worked to carry a bag by following humans without any touch. This robot is by upgrading the trolley to a smart bag carrier with a human detection system, there will be a reduction in the risk for the virus to spread. It is because the bag carrier will automatically move without any touching. Furthermore, with the smart bag carrier, it will again ease the burden of hotel workers. Moreover, the worker will not feel any pain because it does not have to use energy to push the trolley. The main objective of this project is to design a smart luggage bag carrier that can bring the luggage bag automatically and can recognize a user without any touches using the Arduino Uno microcontroller and Ultrasonic sensor (HC-SR04). The second one is, to develop a system that can implement at the hotel and help workers to bring the luggage bag easily to the customer room. Lastly, this project can analyze human interaction and movement through positioning and distance. The research contribution for this project is it can implement in many ways and many places such as a supermarket, airport, factory, and hospital. It also can help in reducing the spreading of the virus.